Patterns of Qur'anic Study Approaches for Preventing Radicalism in Singapore - M. Ilham Muchtar; Saifuddin Amin; Jumadil (Institut Agama Islam Negeri (IAIN) Keiri, 2024)
This study explores the paradigms and approaches employed in Quranic studies to mitigate radicalism in Singapore. A qualitative descriptive methodology was utilised to examine the patterns of Quranic study. The primary and secondary data sources comprised the Muslim community in the country, alongside relevant literature including books, journals, and research reports. Data collection methods included interviews, documentation, and observation, with subsequent analysis conducted using qualitative data analysis techniques. The findings reveal that while the Muslim community generally enjoys the freedom of religious practice and access to Islamic educational institutions and organisations, the government has instituted regulations to ensure that Quranic study promotes moderate thought, openness, and interreligious harmony. Although the city provides a conducive environment for Quranic studies, measures are in place to maintain social harmony and prevent potential radicalisation. The Majlis Ugama Islam Singapura (MUIS) mandates requirements for preachers, including obtaining permits, demonstrating speaker competency, ensuring appropriate content, providing security assurance, and securing location permits. MUIS employs three main approaches in Quranic study: 1) categorising preachers based on their knowledge, experience, and skills; 2) using interpretive methods such as thematic, linguistic analysis, historical, and comparative approaches, which are regularly evaluated; and 3) monitoring the content of the material through reporting mechanisms and documentation from the start to the end of activities. The study concludes that the approach to Quranic study in the country plays a significant role in shaping understanding and the application of Islamic teachings, underpinned by the values of moderation and religious tolerance.